Exploring cultural identity in diasporic space in Sam Selvon’s The Lonely Londoners, Timothy Mo’s Sour Sweet, and Hanif Kureishi’s The Buddha of Suburbia - Chia, Nicole Marie U (2015)
Human migration is no foreign concept within the international landscape and is a distinctive characteristic of today’s globalized world. It is arguable that cultural identity is not only based on race but also the environment that we live in. This dissertation examines the challenges and development of cultural identity in diasporic communities in today’s globalized context through space and time. Using Sam Selvon’s The Lonely Londoners (1956), Timothy Mo’s Sour Sweet (1982) and Hanif Kureishi’s The Buddha of Suburbia (1990), this thesis explores the intricate process and challenges migrants experience through the analysis of the novels’ form. The examination of form is integral in attaching meaning to the characters and their experiences in the novel as this dissertation proves that cultural identity is a constant process and development that is not only about roots, but routes.